From Marxism to Idealism. The Transformation of Reception of Marx in the Creativity of Semen Frank - Obolevitch, Teresa (Hybris, 2018)
This article is dedicated to the problem of philosophical development of famous Russian philosopher Semen Frank (1877-1950) at his early stage of creativity. To begin with, Frank shared the conception of so- called legal Marxism which was very popular in Russia in the end of the 20th century. Gradually, he gave up this view and started publishing at first on Neo-Kantian topics and, later on, as religious thinker. Nevertheless, Frank continued interest in Marxism, even if he criticized it.